Analysis of Student Needs for Context-Based Teaching Materials and Creativity to Improve Science Literacy of Elementary School Students - Rahmani (Jurnal Serambi Ilmu, 2024)
Teaching materials are one of the important components needed in the learning process. With the appropriate teaching materials, it is hoped that it can help the smooth running of learning activities. Science is a compulsory subject for elementary school students. Science contains all things related to nature. Teaching materials that have been used in learning activities are teaching materials made by the government. The purpose of this study was to determine the needs of students for context-based teaching materials and creativity to improve the scientific literacy of elementary school students. The research subjects were students from several elementary schools in Peukan Bada District, 25 students were used as the source of interview data. Data were collected using interviews and open questionnaires for students. The research data were analyzed descriptively qualitatively. Based on the research data, it can be concluded that it is necessary to develop context-based teaching materials and creativity. Context and creativitybased teaching materials were chosen because they can facilitate students to learn, both with educators and independently. Context-based teaching materials and creativity are teaching materials that are packaged in a comprehensive and schematic manner. This study is also part of a study on the development of teaching materials on the topic of human and animal organism.